Energy features of CO2-cycles during oxygen combustion of methanol - P. A. Shchinnikov; I. S. Sadkin; O. V. Borush; R. V. Romanenko (Известия высших учебных заведений: Проблемы энергетики)
The PURPOSE of the work is to determine the mass-flow characteristics of working substances and energy indicators of an installation based on a CO2 cycle with a two-stage pressure increase (Allam cycle) during oxygen combustion of methanol.METHODS. A research methodology is presented in which the mass-flow characteristics of working substances are determined based on the reactions of combustion and synthesis of methanol and electrolysis of water. These reactions are basic for ensuring operational processes in the installation. The method is based on the molar ratios of substances participating in reactions under stoichiometric conditions. Using the thermodynamic parameters of the cycle being implemented and at a given installation power, the consumption of the working fluid, the share of carbon dioxide renewal in the cycle, the amount of methanol produced in the synthesis unit, the amount of fresh methanol, the amount of hydrogen produced in the water electrolysis unit and the amount of oxygen are determined, necessary to ensure fuel combustion processes. At the same time, the amount of commercial hydrogen is determined. Electricity consumption for own needs is determined using regulatory methods and data from equipment manufacturers.RESULTS. The article shows that with similar values of thermal efficiency of CO2 cycles based on oxygen combustion of methane and methanol, the amount of carbon dioxide removed from the cycle for disposal is 11% less. It has been shown that a CO2 cycle operating on methanol is capable of producing commercial hydrogen simultaneously with electricity generation. The specific electricity consumption for hydrogen production is 22% less than for its production without combination with the CO2 cycle.